2014
DOI: 10.1016/j.jtcvs.2013.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of acute kidney injury within 30 days of cardiac surgery

Abstract: Acute kidney injury after cardiac surgery can be predicted using preoperative risk factors alone or, with greater accuracy, using pre-, peri-, and early postoperative risk factors. The ability to identify high-risk individuals can be useful in preoperative patient management and for recruitment of appropriate patients to clinical trials. Prediction in the early stages of postoperative care can guide subsequent intensive care of patients and could also be the basis of a retrospective performance audit tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 25 publications
3
79
0
Order By: Relevance
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…The ROC-AUC varied between 0.77 and 0.84 in both internal and validation cohorts and most of the studies reported an array of common predictors using mainly logistic regression analysis as a computational tool. Two more recent studies in the United Kingdom and Australia used larger data registries for development and validation of predictive scores that included several intraoperative variables, although model performance remained less than 0.82 73,74 . For patients undergoing non-cardiac surgery few preoperative predictive models were developed, using either only severe AKI as an end-point or limiting inclusion to a specific type of surgery 22,75 .…”
Section: Clinical Risk Scoresmentioning
confidence: 99%
“…Transcatheter aortic valve replacement (TAVR) is an emerging alternative to surgery for patients with severe aortic stenosis perceived to be at increased risk for perioperative mortality . TAVR patients are universally elderly and often possess numerous comorbid conditions, many of which are known risk factors for acute kidney injury (AKI) after cardiac procedures . The incidence of AKI after TAVR is consequently high, with AKI occurring in 8% to 42% of cases .…”
Section: Introductionmentioning
confidence: 99%